The suffering of arts entrepreneurs: Will fine art students be educated on how to become successfully self-employed? - Marco Thom (Journal of Education and Training Studies, 2014)
The aim of the study is to show whether, how and to what extent fine art students will be equipped with entrepreneurial skills and therefore be educated on how to make a living as a practicing artist. A comprehensive and comparative analysis of Fine Art degree programmes and extra-curricular training offerings at higher education institutions (HEIs) in the UK and Germany was carried out. By using various key performance indicators this study shows evidence that the crucial entrepreneurial skills for a successful self-employment in the arts are only taught to a very small extent if even at all.
Keywords: A220; A23; 330; arts entrepreneurs; entrepreneurial skills; fine art students; self-employment; higher education institutions